King of the road : true tales from a legendary ice road trucker - Debogorski, Alex, 1953- (Hoboken, N.J. : Wiley, 2010)
"The highest-rated reality show ever to hit the History channel, Ice Road Truckers follows the heart-pounding adventures of the tough-as-nails truckers who risk peril every day to deliver goods and supplies in Alaska and across Canada's frozen north."--Provided by publisher.
Acknowledgments. -- Prologue. -- 1 Early Days. -- 2 The Open Road Beckons. -- 3 Time to Grow Up. -- 4 Life Is a Cabaret. -- 5 A Driven Man. -- 6 Into the Kingdom of Ice. -- 7 Hollywood Comes to Town.
Keywords: Debogorski, Alex, -- 1953-; Ice road truckers (Television program); Truck drivers -- Canada -- Anecdotes; Ice crossings -- Alaska -- Anecdotes; Ice crossings -- Canada -- Anecdotes; Trucking -- Anecdotes